A Case Report of Gastric Oral Contrast-enhanced Ultrasonography in the Diagnosis of Eosinophilic Gastroenteritis in Adults - Qiu, Lanyan; Liu, Dong (Current Medical Imaging, 2024)
Introduction Eosinophilic gastroenteritis (EGE) is a rare immune-mediated chronic inflammatory disorder, which is classified into 3 types according to the affected gastric wall layer. The serosal-type EGE is the least common type. Gastric oral contrast-enhanced ultrasonography (OCEUS) may show some specific changes in the serosal-type EGE. Herein, we reported OCEUS findings in a serosal-type EGE case. Case Presentation A 60-year-old man with unexplained abdominal pain accompanied by diarrhea, which lasted for half a month, consulted the hospital. Laboratory findings revealed peripheral eosinophilia and elevated carbohydrate antigen 125(CA125). OCEUS showed a thickened gastric antrum wall and ascites, with distinct layers (thickening of the muscularis propria layer was most obvious), which is rare and specific. Endoscopy showed normal mucosa of the esophagus and stomach and scattered hyperemia spots in the mucoua of the duodenal bulb and small intestine. Microscopy evaluation revealed few eosinophils infiltration in the lamina propria. A large number of eosinophils were seen in peritoneal lavage fluid and the greater omentum. Eventually, the patient was diagnosed with serosal type EGE. Conclusion Significant thickening of the digestive tract walls and ascites at ultrasonography (US)-examination, with distinct layers and predominant thickening of the muscularis propria layer at OCEUS, can indicate EGE.
Keywords: Eosinophilic gastroenteritis